Herringbone stitch technique versus interrupted suturing technique for rectus closure in emergency laparotomy: A comparative study - Arvind Kumar Shukla; Avinash Gautam; Saranshi Shrivastava; Sagar Arora; Ramendra Singh; Rishi Kumar Athya; Rijul Marwah (Asian Journal of Medical Sciences, 2024)
Background: Midline laparotomy incisions provide easy and rapid access to the peritoneal cavity in case of emergency surgery and effective closure of the abdominal wall is crucial for optimal healing and reduced complications. Secure abdominal wall closure after any laparotomy is every surgeon’s aim. Aims and Objectives: The aim of the study was to choose the better method of rectus closure by comparing the herringbone stitch technique with the interrupted suturing technique for rectus closure in emergency laparotomy. Materials and Methods: Fifty patients who underwent midline emergency laparotomy at MGM Medical College and MY Hospital, Indore, between January 2023 and April 2023 were included in our study. In 25 patients (Group A) herringbone stitch technique was used whereas in the other 25 patients (Group B) interrupted suturing technique for rectus closure was used and they were assessed based on the incidence of surgical site infection (SSI), superficial wound dehiscence, fascial dehiscence, and incidence of incisional hernia. Results: The incidence of SSI was comparable in both groups but the incidence of superficial wound dehiscence, fascial dehiscence, and incisional hernia is less in Group A. Conclusion: The herringbone stitch technique is better as compared to the interrupted suturing technique for rectus closure in emergency laparotomy.